Peningkatan Kemampuan Pemecahan Masalah Matematis Siswa Melalui Penerapan Pembelajaran Inkuiri Berbantuan Puzzle - Richa Karlina Nofitasari; Ratri Rahayu; Jayanti Putri Purwaningrum (Universitas Muria Kudus, 2020)
This research aims to describe the improvement (1) mathematics problem solving abilities, (2) improve student learning activity, and (3) teacher teaching skill in implementing inquiry learning model assisted by segita puzzle under material perimeter and area of square, rectangle, and triangle. The methods of collecting data were test, observation, interview, and documentation. The data analysis of the research was quantitative and qualitative analysis. The findings showed improvement of the problem solving abilities average. In cycle I, it was 68, with percentage 71%, categorized well. It improved into 85 in cycle II with percentage 86%, categorized well. Student learning activity average in cycle I it was 80 with predicate sufficient. It improved into 88 with predicate well in cycle II. Teacher teaching skill in cycle I was 95, or 74%, categorized sufficient. In cycle II, it improved into 117.65, or 87%, categorized well. It is concluded that the implementation of inquiry model assisted by segita puzzle could improve mathematics problem solving abilities, student learning activity, and teacher teaching skill.